2013
DOI: 10.1038/tp.2012.137
|View full text |Cite
|
Sign up to set email alerts
|

A role for the extended amygdala in the fear-enhancing effects of acute selective serotonin reuptake inhibitor treatment

Abstract: Selective serotonin reuptake inhibitors (SSRIs) are reported to exacerbate symptoms of anxiety when treatment is initiated. These clinical findings have been extended to animal models wherein SSRIs also potentiate anxiety and fear learning, which depend on the amygdala. Yet, little is known about the role of specific amygdalar circuits in these acute effects of SSRIs. Here, we first confirmed that a single injection of fluoxetine 1 h before auditory fear conditioning potentiated fear memory in rats. To probe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 88 publications
5
42
1
Order By: Relevance
“…While the serotonergic modulation of fear memory has been extensively studied [27, 3237], these experiments are the first to examine the effects of chronic, preconditioning fluoxetine on both the contextual and auditory fear memory of mice. Using two differing experimental paradigms, the fluoxetine treatment of adult mice impaired their contextual fear memory, but spared auditory fear memory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the serotonergic modulation of fear memory has been extensively studied [27, 3237], these experiments are the first to examine the effects of chronic, preconditioning fluoxetine on both the contextual and auditory fear memory of mice. Using two differing experimental paradigms, the fluoxetine treatment of adult mice impaired their contextual fear memory, but spared auditory fear memory.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, auditory freezing tends to be increased or unaltered by SSRI treatment [27, 34, 37, 38]. In these previous studies, decreased contextual freezing was attributed to an anxiolytic effect for the medication [3336].…”
Section: Discussionmentioning
confidence: 99%
“…Benzodiazpine administration also reduced CRF-enhanced startle, suggesting that the effect generalizes to other paradigms that measure BNST-mediated responses (Swerdlow et al, 1986). Another study showed that an acute injection of fluoxetine into the BNST of fear conditioned rodents enhanced fear acquisition and this effect was not seen for injections into the amygdala (Ravinder et al, 2013). Together, these findings suggest that the BNST and BNST-mediated behaviors respond uniquely to pharmacological agents, although much remains to be learned about the exact nature of these relationships and the implications for clinical practice.…”
Section: Building Blocks For Human Studies: Current Evidence In Rodenmentioning
confidence: 96%
“…Ravinder et al (522) confirmed the fear-enhancing effect of SSRIs, studying the possible role of the Arc gene in the CE in this, and examine the involvement of the extended amygdala, not just the amygdala in SSRI effects. They found that the also prototypical SSRI fluoxetine increases Arc in the CE, and its administration into the bed BNST, a part of the "extended amygdala" (13), produces a fear potentiation similar to that induced by systemic administration of the drug, also accompanied by an Arc increase in the CE.…”
Section: Serotonin (5-hydroxytryptamine 5ht)mentioning
confidence: 99%